Indicadores de risco associados à presença e severidade da periodontite apical em uma população rural do sul do Brasil - Camponogara, Jeanni Gonçalves (2023)
Oral diseases represent the highest prevalence among non-communicable diseases, impacting 45% of the worldwide population. Among these non-communicable oral diseases, Apical Periodontitis (AP) emerges as an inflammatory ailment affecting the periapical tissues, triggered by microbial infection within the root canal system. The occurrence of AP has demonstrated correlations with specific systemic illnesses, smoking habits, as well as sociodemographic and economic factors. In light of this, the primary aim of the first study was to evaluate the correlation between medical and behavioral variables and the presence of AP, whereas the second study aimed to assess the association between sociodemographic and economic variables and the presence of AP, both within a representative rural population. These investigations comprised two cross-sectional studies, utilizing a sample of individuals ranging in age from 18 to 93 years, obtained from an epidemiological survey conducted in the rural area of Rosário do Sul, RS, Brazil, between March 2015 and May 2016. Sociodemographic, economic, medical, and behavioral data were collected through structured questionnaires. AP was assessed and classified based on the evaluation of periapical radiographs using "The Periapical Index" and subsequently categorized as a dichotomous variable (presence or absence). Family income was standardized in terms of minimum wages. Logistic regression analyses adjusted were performed in both cross-sectional studies to identify the variables associated with AP. The sample comprised 540 individuals, with a mean age of 47.3 years, of whom 50.2% were male, and 60.4% exhibited AP. In the first study, the presence of AP was independently associated with age (odds ratio [OR] = 1.018, 95% confidence interval [CI]: 1.001-1.035, p = 0.041), active or former smoking (OR = 2.109, 95% CI: 1.256-3.540, p = 0.005), and diabetes mellitus (DM) or pre-diabetes (OR = 1.696, 95% CI: 1.164-2.471, p = 0.006). In the second study, the presence of AP was associated with age (odds ratio [OR] = 1.029, 95% confidence interval [CI]: 1.013-1.046, p < 0.001), non-white skin color (OR = 1.497, 95% CI: 1.019-2.197, p = 0.040), and family income < 1 minimum wage (OR = 2.330, 95% CI: 1.570-4.693, p = 0.018). In the second study, the presence of AP was associated with age (odds ratio [OR] = 1.029, 95% confidence interval [CI]: 1.013-1.046, p < 0.001), non-white skin color (OR = 1.497, 95% CI: 1.019-2.197, p = 0.040), and family income < 1 minimum wage (OR = 2.330, 95% CI: 1.570-4.693, p = 0.018). The first study identified an association between advanced age, pre-diabetic or diabetic status, and current or former smoking habits with the presence of AP. The second study demonstrated that advanced age, non-white skin color, and lower family income were associated with an increased likelihood of AP. These findings emphasize the significance of implementing targeted preventive and therapeutic strategies for these high-risk groups, aiming to reduce the incidence and severity of AP and alleviate oral health disparities.